2022
DOI: 10.3390/polym15010038
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Effects of Manufacturing Parameters on Mechanical Properties of Additively Manufactured PA and CF-Reinforced PA Materials

Abstract: Nowadays, 3D printers, which have a wide range of applications, continue to become widespread and are more and more common. As a result, in addition to the visuality of the parts produced with this method, their mechanical properties have gained importance depending on where they are used. In addition to the many conveniences, it provides during the design and production phases according to traditional methods the features of the printing parameters used, especially the printing direction and angle, which vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
4
8
1
1
Order By: Relevance
“…Moreover, Tough PLA had a more ductile behavior, with higher elongation values regardless of the raster orientation, as can be observed in Figure 7 a,b, where a comparison between the stress–strain curves of the materials and raster orientations tested is presented. This behavior was consistent with the findings of other authors [ 20 , 21 , 23 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, Tough PLA had a more ductile behavior, with higher elongation values regardless of the raster orientation, as can be observed in Figure 7 a,b, where a comparison between the stress–strain curves of the materials and raster orientations tested is presented. This behavior was consistent with the findings of other authors [ 20 , 21 , 23 ].…”
Section: Resultssupporting
confidence: 94%
“…A complete rupture occurred on the UltraFuse PAHT CF 15 specimens. Similar damage was observed for UltraFuse PAHT CF15 by Tutar [ 23 ].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In today’s world, many manufacturing sectors increasingly require cost-effective, high-quality, customized components with the necessary mechanical features [ 1 , 2 ]. Additive manufacturing (AM) or 3D printing represents a crucial advancement in producing components featuring intricate geometries and desired characteristics [ 3 , 4 ]. Unlike conventional machining technologies, AM technologies enable the manufacturing of the physical part from three-dimensional computer-aided data, layer by layer, using as much material as needed [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers investigated the effect of printing parameters and post‐processing on the mechanical properties of 3D printed parts 3–9 . From this research, it can be concluded that optimizing the process parameters, post‐processing such as heat treatment, or using reinforced materials can improve mechanical strength 10–12 . In the majority of the studies, the time‐independent mechanical properties obtained by tensile, compression, bending, impact testing, or other properties like surface roughness and wear has been investigated.…”
Section: Introductionmentioning
confidence: 99%